The Risk of Cardiovascular Diseases in Axial Spondyloarthritis. Current Insights - Toussirot, Eric (Frontiers in Medicine, 2021)
There is an increased cardiovascular (CV) risk in axial spondyloarthritis (axSpA), leading to increased CV mortality and morbidity in these patients. The factors that may explain this enhanced CV risk in axSpA are multiple, including traditional CV risk factors such as smoking, but also the inflammatory process and probably the use of non-steroidal anti-inflammatory drugs (NSAIDs). The CV involvement of axSpA may be detected at an early and pre-clinical stage, using non-invasive techniques. While NSAIDs play a deleterious role in the CV risk of axSpA, TNF inhibitors seem to have a beneficial impact, but this remains to be demonstrated in specific clinical studies. More data are needed to determine the potential effects of IL-17 inhibitors on the CV risk of axSpA. CV comorbidity has been mainly assessed in the radiographic form of axSpA, while limited data are available in patients with the non-radiographic form. The current management of axSpA must consider this CV comorbidity according to the EULAR recommendations. Rheumatologists play a determinant role in the detection of CV risk and current management of these patients is focused on the control of disease activity, suppression of inflammation, screening for and management of traditional CV risk factors, as well as the restriction of NSAID use.